A Comparative Analysis of Foot Orthosis Manufacturing Results Using the Gips Roll Casting and Custom 3D Scan Method - Anggriani, Atika Febri; Utomo, Prasetyo Catur (Jurnal Keterapian Fisik, 2024)
Background: A musculoskeletal disorder that is often found is flatfoot. In handling various problems that occur in the foot, intervention can be given by using custom foot orthoses. The method often used in the process of making custom foot orthoses is the casting method. In recent years, advanced technology has continued to emerge and has really helped many manufacturers make foot orthoses with 3D scan tools and 3D printers. The aim of this research is to analyse the results of making foot orthoses using the cast roll casting method and a custom 3D scan.                              Methods: The method used is experimental research with purposive sampling. The inclusion criteria were subjects with flat feet, and the exclusion criteria were subjects with deformities other than flat feet. The population was 38 people, and the respondent was 8. To determine the accuracy of measurements using statistical analysis with the Mann-Whitney test. Then the results of the two casting methods were fabricated and compared with measurements, as well as the efficiency of the foot orthosis manufacturing process using each method. Results: The p value was 0.967 in the measurements with plaster roll media and 1.000 in the measurements with 3D scan media based on the respondent's original foot. Conclusion: There is no significant difference between the two methods. So the 3D scan method can also be used as a method for developing custom foot orthosis fabrication processes to improve the development of science and technology in the field of prosthetic orthotics.